An attempt to induce an immunomodulatory effect in rowers with spirulina extract - Juszkiewicz, A.; Basta, P.; Petriczko, E.; Machalinski, B.; Trzeciak, J.; Luczkowska, K.; Skarpanska-Stejnborn, A. (Journal of the International Society of Sports Nutrition, 2018)
Background: The aim of this study was to analyze the response of selected components of the immune system in rowers to maximal physical exercise, and to verify if this response can be modulated by supplementation with spirulina (cyanobacterium Spirulina platensis). Method